Effect of added fat on performance of growing-finishing pigs in commercial conditions - Young, M.G.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,040 pigs (half barrows and half gilts) was used in a 42-day experiment conducted in a commercial research facility to determine the influence of graded levels of added fat on growth performance, feed cost per pound of gain and margin over feed of growing-finishing pigs. The four dietary treatments were based on level of added dietary fat (0, 2, 4, or 6%), with the diets fed for a six-week period from 158 to 232 lb. Adding fat to the diet for pigs weighing 158 to 232 lb decreased ADFI, improved feed efficiency, increased cost per pound of gain and had no effect on income over feed cost. The economics of whether fat should be added to the growing finishing pig diet will depend on the cost of corn, soybean meal and fat. The results of this experiment demonstrate that, with current prices, the lowest cost per pound of gain was obtained when no fat was added to the diet for pigs from 158 to 232 lb. But because of the numerically greater ADG income over feed cost (IOFC) was numerically similar when fat was added to the diet.
Keywords: Added fat; Growing-finishing pigs; Swine